2012
DOI: 10.1095/biolreprod.111.094771
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Effects of Early Pregnancy with Human Interferon, Alpha 2 (IFNA2), on Gene Expression in Bovine Endometrium1

Abstract: Interferon tau (IFNT), a type I IFN similar to alpha IFNs (IFNA), is the pregnancy recognition signal produced by the ruminant conceptus. To elucidate specific effects of bovine IFNT and of other conceptus-derived factors, endometrial gene expression changes during early pregnancy were compared to gene expression changes after intrauterine application of human IFNA2. In experiment 1, endometrial tissue samples were obtained on Day (D) 12, D15, and D18 postmating from nonpregnant or pregnant heifers. In experim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
109
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 95 publications
(117 citation statements)
references
References 90 publications
(108 reference statements)
6
109
1
1
Order By: Relevance
“…It is only when IFNT secretion from the conceptus is sufficient to induce the pregnancy recognition response in both the endometrium and in the extra uterine environment, that divergences between the pregnant and non-pregnant uterus are established. In general, these differences are detectable by Day 15 or Day 16 of pregnancy (Forde et al, 2011b;Bauersachs et al, 2012) and the major changes identified include response to a Type I Interferon, of which IFNT is one. This includes the up-regulation of 'classical' interferon-stimulated genes (ISGs) such as ISG15, (Johnson et al, 1998), MX1 and MX2 (Hicks et al, 2003), OAS1, BST2, B2M, CXCL10, STAT1, STAT2, PTX3, EIF4E, USP18 (Forde et al, 2011b) Indeed in the last number of years there have been quite a number of large transcriptomic studies performed on gene expression changes in the endometrium of pregnancy compared with non-pregnant or cyclic heifers.…”
Section: Conceptus-induced Effects On the Endometriummentioning
confidence: 99%
See 3 more Smart Citations
“…It is only when IFNT secretion from the conceptus is sufficient to induce the pregnancy recognition response in both the endometrium and in the extra uterine environment, that divergences between the pregnant and non-pregnant uterus are established. In general, these differences are detectable by Day 15 or Day 16 of pregnancy (Forde et al, 2011b;Bauersachs et al, 2012) and the major changes identified include response to a Type I Interferon, of which IFNT is one. This includes the up-regulation of 'classical' interferon-stimulated genes (ISGs) such as ISG15, (Johnson et al, 1998), MX1 and MX2 (Hicks et al, 2003), OAS1, BST2, B2M, CXCL10, STAT1, STAT2, PTX3, EIF4E, USP18 (Forde et al, 2011b) Indeed in the last number of years there have been quite a number of large transcriptomic studies performed on gene expression changes in the endometrium of pregnancy compared with non-pregnant or cyclic heifers.…”
Section: Conceptus-induced Effects On the Endometriummentioning
confidence: 99%
“…This includes the up-regulation of 'classical' interferon-stimulated genes (ISGs) such as ISG15, (Johnson et al, 1998), MX1 and MX2 (Hicks et al, 2003), OAS1, BST2, B2M, CXCL10, STAT1, STAT2, PTX3, EIF4E, USP18 (Forde et al, 2011b) Indeed in the last number of years there have been quite a number of large transcriptomic studies performed on gene expression changes in the endometrium of pregnancy compared with non-pregnant or cyclic heifers. Despite the different platforms used for analysis, breed of animal and different data analysis methods Bauersachs et al (2012) used gene set enrichment analysis to reveal a conceptus-induced signature in the endometrium across numerous studies on Days 15, 16, 17, 18 and 20.…”
Section: Conceptus-induced Effects On the Endometriummentioning
confidence: 99%
See 2 more Smart Citations
“…Generally, genes encoding trophoblast kunitz domain proteins, pregnancyassociated glycoproteins, cytoskeletal transcripts, heat shock proteins and calcium-binding proteins had highest expression levels at each of these stages of development (Lonergan and Forde, 2014;Mamo et al, 2011). Bauersachs et al (2012) carried out a gene set enrichment analysis of several global transcriptomic datasets from days 15, 16, 17, 18 and 20 of the oestrus cycle or pregnancy and identified a conceptus-induced signature in the endometrium during the process of pregnancy recognition. Together with progesterone (P4), IFNT regulates endometrial gene expression necessary for the establishment of the proper uterine environment during the implantation period (Klein et al, 2006).…”
Section: Molecular Response Of Maternal Endometrium To the Embryomentioning
confidence: 99%